Kepimpinan islam guru besar dan hubungannya dengan iltizam guru di SK dan SARS - Yusof, Roslan (2016)
This study aims to meet three main objectives: to conceptualise and validate items and instruments which have been developed to measure Islamic leadership and teachers' commitment in SK and SARS; to compare the dimensions of Islamic leadership practices among Headmasters in SK and SARS and teachers' commitment practices in both types of schools concerned and; to examine the relationship between Islamic leadership amongst Headmasters in SK and SARS and teachers' commitment in SK and SARS. Based on the literature review, Islamic leadership has been conceptualised as the following 6 dimensions, namely; (i) fairness (ADL); (ii) benevolence (IHS); (iii) integrity (INT); (iv) introspection (MUD); (v) conference (MUS); and (vi) vision (WWS). Meanwhile, teachers' commitment refers to 4 dimensions of: (i) teachers' commitment to school (IKS); (ii) teachers' commitment to students (IKM); (iii) teachers' commitment to teaching (IKT); and (iv) teachers' commitment to profession (IKP). A questionnaire was developed, validated, and administered to 300 respondents to get their insights on Islamic leadership and teachers' commitment. The study involved teachers in SK and SARS, from the states of Perlis, Kedah, Pulau Pinang, and Perak.